EFFECT OF NATURAL MINERAL BISCHOFITE CONTAINING PREPARATION ON THE ORAL MICROFLORA - Skrypnykov, P.N.; Skrypnikova, T.P.; Loban, G.A.; Gancho, O.V.; Khavalkina, L.M.; Zezekalo, S.V. (World of Medicine and Biology, 2020)
The oral cavity can be considered as an ecological system complex in which external factors (biological, individual, social) interact with internal ones (periodontium, bacterial community, local immune system, oral epithelium). If the favorable conditions arise, one or another disease of the oral mucosa may be developed and must be adequately treated. The arsenal of drugs is large and requires the doctor’s knowledge, skills in using of the most optimal means and providing the appropriate recommendations to the patient. We studied the efficacy of the oral care product Antiqua Mare MAX, containing natural mineral Poltava’s Bischofite, on the representatives of the oral microflora. To achieve this goal, museum strains of E. coli ATCC 25922, S. aureus ATCC 25923, S. epidermidis ATCC 14990, E. faecalis ATCC 29212, M. lysodeicticus ATCC 4698 and C. albicans ATCC1023 were used. As a control, a well-known antimicrobial agent 0.02% aqueous solution of chlorhexidine bigluconate was used. The ability of the Antiqua Mare MAX drug to inhibit the growth of museum cultures of the yeast-like fungi, colon bacilli, enterococci, micrococci, epidermal and golden staphylococci in the liquid medium was shown to coincide completely in three repeated determinations during the study of the effect of Bischofite containing oral care product. The fungiostatic activity of the studied preparation Antiqua Mare MAX exceeded the effect of 0.02% solution of chlorhexidine bigluconate by 4 times (p